2015
DOI: 10.1080/07448481.2014.1003377
|View full text |Cite
|
Sign up to set email alerts
|

The Inability of Self-affirmations to Decrease Defensive Bias Toward an Alcohol-Related Risk Message Among High-Risk College Students

Abstract: Objective To examine the efficacy of a self-affirmation task in deterring college alcohol misuse and the importance of pre-existing beliefs in predicting subsequent behavior change. Participants Heavy drinking undergraduates (N=110) participated during the 2011–2012 academic year. Methods Participants were randomized to complete an affirmation or control task before reading an alcohol risk message. Alcohol-related beliefs and behaviors were assessed. Participants completed a two-week online follow-up asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 24 publications
5
24
0
Order By: Relevance
“…Similarly, Meier et al (2015) reported no significant differences between non-affirmed and affirmed participants on measures of problem importance, perceived risk and self-reported number of weekly drinks and peak quantity consumed at two-weeks follow-up in a sample of heavy drinking students who read a health-risk message about alcohol. Overall, findings for the impact of self-affirmation manipulations on the processing and acceptance of health-risk messages about alcohol in university students are mixed.…”
Section: Self-affirmation and Implementation Intentionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, Meier et al (2015) reported no significant differences between non-affirmed and affirmed participants on measures of problem importance, perceived risk and self-reported number of weekly drinks and peak quantity consumed at two-weeks follow-up in a sample of heavy drinking students who read a health-risk message about alcohol. Overall, findings for the impact of self-affirmation manipulations on the processing and acceptance of health-risk messages about alcohol in university students are mixed.…”
Section: Self-affirmation and Implementation Intentionsmentioning
confidence: 92%
“…Most tests of the effects of self-affirmation on alcohol-related cognitions and behaviour in university students (Ferrer et al, 2012;Harris & Napper, 2005;Klein et al, 2011, Meier et al, 2015 have used a values essay to manipulate self-affirmation in which participants are instructed to select their most important value and write about why it is important to them (Crocker, Niya & Mischkowski, 2008). Crocker et al (2008) reported that between 48% (Study 1) and 67% (Study 2) of students chose Òsocial life-relationshipsÓ as their most important value to write about.…”
Section: Self-affirmation and Implementation Intentionsmentioning
confidence: 99%
“…These strategies appear to counteract defensiveness, enabling appropriate processing of self-threatening information (Cohen and Sherman, 2014). Effects of self-affirmation have been examined in studies of alcohol-related threatening health information (Armitage et al, 2011, Armitage et al, 2014, Meier et al, 2015, Harris and Napper, 2005, Klein and Harris, 2009, Klein et al, 2011. These studies tend to support self-affirmation theory, showing for example, increased subjective fear and intention to reduce consumption following threatening health information in self-affirmed participants, although these effects may depend on participants' habitual level of drinking (Scott et al, 2013, Harris and Napper, 2005, Klein and Harris, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous relevant studies included only women (Harris and Napper, 2005, Klein and Harris, 2009, Klein et al, 2011, while those that included both men and women did not examine gender-effects (Meier et al, 2015, Armitage et al, 2011, Scott et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Although self-affirmation is a powerful intervention tool, it is not always effective (e.g., Fry & Prentice-Dunn, 2005; Meier et al, 2015), and meta-analyses demonstrate a significant but modest effect (Epton et al, 2015; Sweeny & Moyer, 2015). Variations in effect suggest that self-affirmation’s effectiveness may be moderated by individual differences or psychological factors (e.g., perceived susceptibility; see Good et al, 2011; Griffin & Harris, 2011; Hall, Zhao, & Shafir, 2014; Klein et al, 2011).…”
mentioning
confidence: 99%